The genus Gymnotus (Gymnotiformes: Gymnotidae) in Argentina. How bad taxonomy results in poor regulations and no conservation - Casciotta, Jorge Rafael (2013)
Four species of the genus Gymnotus are present in Argentina: G. inaequilabiatus, G. omarorum, G. pantanal, and G. sylvius, the last three species being recorded for the first time in freshwater courses. Gymnotus omarorum, G. pantanal, and G. sylvius together with others of the genus Brachyhypopomus are the group of fishes that bear the greatest impact in the trade as live bait for sport fishing in the northeastern region of Argentina. Within this large area, only the provinces of Chaco, Corrientes, and Formosa have regulations for the catch, trade, and sale of species as live bait. Unfortunately, the species covered by legal regulations are Gymnotus carapo and Brachyhypopomus brevirostris, neither of which occurs in freshwater habitats of Argentina. Comments are included as to how this bad taxonomy affects the regulations and conservation status of these species.